Judicial Independence in British North America, 1825–67: Constitutional Principles, Colonial Finances, and the Perils of Democracy. (23rd May 2016) - Phillips, Jim
Abstract : It is well known that "formal" judicial independence—appointment on good behavior rather than at pleasure—was established in Britain with the 1701 Act of Settlement, and, like many other aspects of the English constitution, not exported to the colonies of either the First or the Second Empire. Its absence formed one of the allegations against the crown in the American Declaration of Independence, and the Constitution of the New Republic accordingly included a federal judicial independence provision. British imperial policy in North America after the Revolution regarding judges continued as before, so that formal judicial independence was not established until 1834, and then only in Upper Canada (now Ontario). In the other three principal British North American colonies this was later still. What is now Quebec (Lower Canada) received good behavior appointments in 1843, and Nova Scotia in 1848. In the other colonies that joined the Canadian Confederation in 1867 (New Brunswick) or within a few years afterwards (British Columbia, Manitoba, and Prince Edward Island), good behavior appointments were introduced for the first time only when the colony joined Confederation.